2020
DOI: 10.1177/1526602820962484
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Volumes After Endovascular Repair of Ruptured vs Intact Aortic Aneurysms: A Retrospective Observational Study

Abstract: Purpose To compare changes in abdominal aortic aneurysm (AAA) sac volume between endovascular aneurysm repairs (EVAR) performed for ruptured (rEVAR) vs intact (iEVAR) AAAs and to determine the impact of early volume shrinkage on future complications. Materials and Methods A retrospective analysis was performed of all patients undergoing standard infrarenal EVAR from 2002 to 2016 at a tertiary referral institution. Only patients with degenerative AAAs and with 30-day and 1-year computed tomography angiography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…14,31,27 In this regard, the ASG score could help improve the selection of patients for follow-up and reduce follow-up costs because patients with low scores have low rates of implant-related complications and therefore do not need a strict follow-up like high-score patients. 32 A strength of the present study is that all cases had the same stent graft system, which makes the cohort on both groups of the ASG score homogenous. Nevertheless, this study has some limitations, including its single-institution retrospective design and the lack of randomization and clinical event committee.…”
Section: Discussionmentioning
confidence: 97%
“…14,31,27 In this regard, the ASG score could help improve the selection of patients for follow-up and reduce follow-up costs because patients with low scores have low rates of implant-related complications and therefore do not need a strict follow-up like high-score patients. 32 A strength of the present study is that all cases had the same stent graft system, which makes the cohort on both groups of the ASG score homogenous. Nevertheless, this study has some limitations, including its single-institution retrospective design and the lack of randomization and clinical event committee.…”
Section: Discussionmentioning
confidence: 97%
“…However, comparative research of sac changes between ruptured and intact AAAs after EVAR has rarely been performed. One recent study showed that there was no difference in the sac behavior between ruptured and intact AAAs treated with EVAR from postoperative 1 year [ 30 ]. Based on this finding, we included patients with ruptured AAAs to reflect real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…Or AAA sac volume can be used as an alternative method. 66,67 Effective oversizing (of the main body of the endograft regarding the post-operative aortic neck diameter):…”
Section: Proposal For Standardisation Of Aortic and Evar Data In Futu...mentioning
confidence: 99%